Biological functions of 5-methylcytosine RNA-binding proteins and their potential mechanisms in human cancers - Zhao, Tingting; Zhang, Zhe; Chen, Zhuo; Xu, Guozheng; Wang, Yongxi; Wang, Fang (Frontiers in Oncology, 2025)
The 5-methylcytosine (m5C) modification is a crucial epigenetic RNA modification, which is involved in the post-transcriptional regulation of genes. It plays an important role in various biological processes, including cell metabolism, growth, apoptosis, and tumorigenesis. By affecting the proliferation, migration, invasion, and drug sensitivity of tumor cells, m5C methylation modification plays a vital part in the initiation and progression of tumors and is closely associated with the poor tumor prognosis. m5C-related proteins are categorized into three functional groups: m5C methyltransferases (m5C writers), m5C demethylases (m5C erasers), and m5C methyl-binding proteins (m5C readers). This paper introduces several common methodologies for detecting m5C methylation; and reviews the molecular structure and biological functions of m5C readers, including ALYREF, YBX1, YBX2, RAD52, YTHDF2, FMRP, and SRSF2. It further summarizes their roles and regulatory mechanisms in tumors, offering novel targets and insights for tumor treatment.